Circularized fluorescent nanodiscs for probing protein–lipid interactions - Qian Ren; Shanwen Zhang; Huan Bao (Communications Biology, 2022)
A fluorescent probe for detecting membrane protein binding and remodeling events is presented, which relies on split-GFP technology to generate circularized nanodiscs useful in membrane protein biophysics and structural biology.